Teknologi Informasi Desa, Upaya Meningkatkan Partisipasi Dan Keterampilan Masyarakat Dalam Pembangunan Desa - Fadilla Oktaviana; Ida Nuraida (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The aim of the Community Service Program, Kuliah Kerja Nyata- Pembelajaran dan Pemberdayaan Kepada Masyarakat (KKN-PPM) is to improve the skills of society in Sindanglaya village, Cinangka. The problem faced does not know the use the waste of plastic to produce the useful and selling value products. The method of implementing this service is through (1) Survey through observation, interviews, and analysis of problems and potential of the village, (2) Training on making paving block from the waste of plastic. The results of this program are increasing knowledge and skills of the community regarding training on making paving block from the waste of plastic. This program is expected to facilitate the community in increasing their knowledge and skills in processing the waste materials into products that are useful and have selling value, therefore that the societies in Sindanglaya become productive communities.